2005
DOI: 10.1182/blood.v106.11.3748.3748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Cytogenetics Abnormalities in Adult Patients with Acquired Aplastic Anaemia.

Abstract: The clinical relevance of cytogenetics abnormalities in aplastic anaemia (AA) patients at time of diagnosis is unclear. We evaluated the clinical course of 81 AA patients with successful cytogenetics at diagnosis and treated with immunosuppressive therapy (IST) from January 1993 to March 2004. A cytogenetic study was considered to be successful if there were a minimum of 15 evaluable metaphases in the absence of a clonal abnormality. Response to IST, survival and later clonal complications in patients with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As discussed previously (see section 2.8) an abnormal cytogenetic clone can be detected in up to 12% of patients with aplastic anaemia at diagnosis (Appelbaum et al, 1989;Socie et al, 2000;Gupta et al, 2006). The most frequently observed abnormalities include trisomy 8, trisomy 6, 5q-and anomalies of chromosomes 7 and 13.…”
Section: Management Of Aplastic Anaemia In the Presence Of An Abnormamentioning
confidence: 83%
See 2 more Smart Citations
“…As discussed previously (see section 2.8) an abnormal cytogenetic clone can be detected in up to 12% of patients with aplastic anaemia at diagnosis (Appelbaum et al, 1989;Socie et al, 2000;Gupta et al, 2006). The most frequently observed abnormalities include trisomy 8, trisomy 6, 5q-and anomalies of chromosomes 7 and 13.…”
Section: Management Of Aplastic Anaemia In the Presence Of An Abnormamentioning
confidence: 83%
“…Often the abnormal clone is small, comprising only a small proportion of total metaphases, and not infrequently, it may be transient and disappear spontaneously or after haematological response to immunosuppressive therapy (Mikhailova et al, 1986;Geary et al, 1999;Piaggio et al, 1999;Socie et al, 2000;Ishiyama et al, 2002;Gupta et al, 2006). From small reported series, the response rates to immunosuppressive therapy appear to be similar to patients with aplastic anaemia who lack an abnormal cytogenetic clone (Mikhailova et al, 1986;Geary et al, 1999;Ishiyama et al, 2002), with good response seen particularly in those patients with trisomies (Gupta et al, 2006). Maciejewski et al (2002) also reported a good response to immunosuppressive treatment in patients who acquired a trisomy 8 after treatment compared with a worse prognosis and high risk of leukaemic transformation for patients with monosomy 7.…”
Section: Management Of Aplastic Anaemia In the Presence Of An Abnormamentioning
confidence: 99%
See 1 more Smart Citation